A STUDY OF GRAMMATICAL ERRORS COMMITTED BY THE ELEVENTH GRADE STUDENTS OF SMK NEGERI 3 DENPASAR IN RESERVATION PRACTICE IN ACADEMIC YEAR 2014/2015 - ., Anak Agung Sagung Intan Yashira Dewi; ., Prof. Dr.I Nyoman Adi Jaya Putra, MA; ., Dr.Sudirman, M.L.S (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
This research aim to: (1) describe kinds of grammatical errors that are most frequently committed by the eleventh grade students of SMK Negeri 3 Denpasar in reservation practice, and (2) explain the sources of errors made by the eleventh grade students of SMK Negeri 3 Denpasar in reservation practice. The subjects of this study were the eleventh grade students of Hotel Accommodation Program at SMK Negeri 3 Denpasar. This research was designed as qualitative descriptive research. This study used video camera, coding sheets, questionnaire, and interview guide as the instruments in collecting data. After the data were collected, the data were transcribed, classified and analyzed, counted, and then the results were described. This study used Abisamra’s and Sawalmeh’s theory to know the types of grammatical errors that commonly made by EFL learners in learning English. The results of this study show that the eleventh grade students of SMK Negeri 3 Denpasar committed eight types of grammatical errors in reservation practice. These errors were verb error, noun error, adjective error, article error, pronoun error, preposition error, sentence fragment error, and word order error. There were 344 errors among 30 students were found and verb error as the most frequently errors committed by the students in reservation practice. The sources of errors were found based on Brown’s theory such as interlingual transfer, intralingual transfer, context of learning, and communication strategies. Interlingual transfer as the highest reason the students committed errors. It was because the students were interfered by the rules of their native language when they speaking in English. keyword : Grammatical Errors, Reservation Practice